To outreach and approach the travellers to engage the uses of first aid kit / Mohamad Fazil Mohamad Kamaruzaman - Mohamad Kamaruzaman, Mohamad Fazil (2015)
This research aims is to increase the awareness among public especially people who are keep travelling within Malaysia or overseas to engage the uses of first aid kit while travelling in any destination. The target group for this research is 50 random respondents who are exposed in any danger when travelling. The advertisement was used in this research as one the recommendation to increase the level of awareness among the public to encourage them to have a safety travel. The methodologies use for this study case included observation, interview and questionnaire to collect data and measure the level of awareness of public regarding the uses and their knowledge in using first aid kit while travelling.